Pseutarin C, a Prothrombin Activator from Pseudonaja textilis Venom: Its Structural and Functional Similarity to Mammalian Coagulation Factor Xa-Va Complex - Rao, Veena S.; Kini, R. Manjunatha (Thrombosis and Haemostasis, 2002)
Several snake venoms contain procoagulant proteins that can activate prothrombin. We have purified pseutarin C, a prothrombin activator from the venom of the Australian brown snake (Pseudonaja textilis). It converts prothrombin to thrombin by cleaving both the peptide bonds Arg274 – Thr275 and Arg323 – Ile324, similar to mammalian factor Xa. It is a protein complex (∼250 Kd) consisting of an enzymatic and a nonenzymatic subunit. These subunits were separated by reverse phase HPLC and their interactions with bovine factor Xa and factor Va were studied. The enzymatic subunit of pseutarin C has a ∼13 fold higher affinity for bovine factor Va (Kd of 11.4 nM for pseutarin C enzymatic subunit – bovine factor Va interaction as compared to a Kd of 147.4 nM for the bovine factor Xa-Va interaction). The non-enzymatic component, however, was unable to activate bovine factor Xa. N-terminal sequence analysis of the catalytic subunit of pseutarin C showed ∼ 60% homology to mammalian factor Xa and ∼78% homology to trocarin, a group D prothrombin activator from Tropidechis carinatus venom. Structural information for the non-enzymatic subunit of pseutarin C was obtained by amino terminal sequencing of several internal peptides. The sequence data obtained indicates that the non-enzymatic subunit of pseutarin C has similar domain architecture like the mammalian factor Va and the overall homology is ∼55%. Thus pseutarin C is the first venom procoagulant protein that is structurally and functionally similar to mammalian factor Xa-Va complex.
Keywords: Prothrombinase complex; eastern brown snake; blood coagulation; thrombin formation; procoagulant toxin